Study of Treatment Families in Battle with Post-Usa Law in Accountability and Sociological MethodA child in conflict with the law, hereinafter referred to as a child, is a child who is 12 (twelve) years old but not yet 18 (eighteen) years old who is suspe - Devendra Singh (Al-Qanṭara, 2022)
A child in conflict with the law, hereinafter referred to as a child, is a child who is 12 (twelve) years old but not yet 18 (eighteen) years old who is suspected of committing a crime. So in this case, a child protection system is needed that can guarantee the growth and development of children who are in conflict with the law. One form of discrimination protection is against children in conflict with the law, namely by diversion and restorative justice. This study aims to see the effectiveness of the application of diversion and restorative justice in Indonesia by taking samples of cases of children that occurred at the Ponorogo Police and the Ponorogo District Court in terms of the Legal and Sociological Accountability approach. The purpose of this study is that the child who is the perpetrator of a crime is able to take responsibility and be held accountable for his actions both for himself, the victim, his family and society, so as to provide a deterrent effect and not repeat the same or different crimes. This research is a qualitative approach, the process is more important than the result, the analysis tends to be done by inductive analysis, and meaning is essential. While the type of research is a case study, namely children in conflict with the law, namely the Police and the Ponorogo District Court. so that it provides a deterrent effect and does not repeat the same or different crimes. The research method used in this study is a qualitative approach, the process is more important than the results, the analysis tends to be carried out by inductive analysis, and meaning is essential. While the type of research is a case study, namely children in conflict with the law, namely the Police and the Ponorogo District Court. so that it provides a deterrent effect and does not repeat the same or different crimes. The research method used in this study is a qualitative approach, the process is more important than the results, the analysis tends to be carried out by inductive analysis, and meaning is essential. While the type of research is a case study, namely children in conflict with the law, namely the Police and the Ponorogo District Court.